Sexual knowledge of Queensland forensic mental health patients: A cross-sectional quantitative study - Brand, Elnike; Tham, Ching; Ratsch, Angela; Heffernan, Edward (Frontiers in Psychiatry, 2023)
Forensic patients with serious mental illnesses (SMI) encounter significant challenges including active symptomatology, associated social and interpersonal impairments, psychotropic medication side effects and institutionalisation, all of which negatively affect sexual functioning and possibly their acquirement of sexual knowledge. Evidence shows an increased prevalence of high-risk sexual behaviour by this group however, there is an absence of literature examining the sexual knowledge of forensic patients. This quantitative cross-sectional study enrolled N = 50 patients currently under the treatment requirements of a Forensic Order and utilised the validated General Sexual Knowledge Questionnaire (GSKQ) to quantify the participants’ sexual knowledge over the domains of physiology, sexual intercourse, pregnancy, contraception, sexually transmitted diseases, and sexuality. Male forensic patients scored lower than females on all domains of sexual knowledge. All participants had reasonable knowledge of physiology, sexual intercourse and sexuality; of concern were poor scores on pregnancy, contraception and sexually transmitted diseases. Thirty-five (70%) of the respondents indicated that they had some limited sex education, mostly at school. Only 6 (12%) received any sexual education from a health professional despite extensive contact with the forensic mental health services across many years. There is a need to assess the deficit in sexual knowledge of forensic patients in order to develop sexual health education, intervention and rehabilitative programmes that cater to the specific needs of this group in order to improve their sexual knowledge, encourage safe and positive sexual experiences, and enhance their quality of life.